2019
DOI: 10.1016/j.ijppaw.2019.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular identification of epibiontic sessilid Epistylis semiciculus n. sp. (ciliophora, Peritrichia) from Procambarus clarkia (Crustacea, Decapoda) in China

Abstract: Data on sessilinasis from Procambarus clarkia are limited. This study investigates sessilid diversity in Hubei Province, China in 2016. Procambarus clarkia pereopods were covered by two sessilid morphotypes in April and May, and the gills were adhered by one of these two morphotypes (morphotype I) in January. Identifying the two morphotypes according to their morphological characters through live observations and protargol-stained method is difficult. Both morphotypes show almost identical morphological charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Although this method is still in its infancy, with immature technology for domestication, it represents a future development trend of the Chinese perch farming industry [3][4][5]. Nonetheless, a challenge lies ahead in the form of Sessilida ciliate infections, which tend to spread during intensive culture conditions [13,15,16]. In the present study, Sessilida ciliates mainly parasitized the dorsal fins of Chinese perch, and generally, they did not directly cause death but rather allowed secondary oomycete infection.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Although this method is still in its infancy, with immature technology for domestication, it represents a future development trend of the Chinese perch farming industry [3][4][5]. Nonetheless, a challenge lies ahead in the form of Sessilida ciliate infections, which tend to spread during intensive culture conditions [13,15,16]. In the present study, Sessilida ciliates mainly parasitized the dorsal fins of Chinese perch, and generally, they did not directly cause death but rather allowed secondary oomycete infection.…”
Section: Discussionmentioning
confidence: 51%
“…Although this method is still in its infancy, with immature technology fo domestication, it represents a future development trend of the Chinese perch farmin industry [3][4][5]. Nonetheless, a challenge lies ahead in the form of Sessilida cilia infections, which tend to spread during intensive culture conditions [13,15,16]. In th…”
Section: Discussionmentioning
confidence: 99%
“…However, the remaining epistylidids still do not form a monophyletic group and their systematics remains confused due to the lack of sufficient morphological and molecular data for most species. Additionally, recent studies have shown that epibiotic epistylidids could provide new insights for exploring the evolutionary routes for sessilids, although compared to their free-living counterparts, investigations of epibiotic epistylidids are limited (Lu et al 2020 ; Song et al 2003 ; Wang et al 2017 ; Zhou et al 2019a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, very different topics about ciliates and their hosts have been developed as shown: symbiotic interactions [epibiotic, hyperepibiotic, commensals, parasites (obligates and facultatives)], codiversification: [29][30][31][32][33][34][35][36][37]. Morphology (variation, molecular characterization): [38], clevellandellid, Nyctotheroides; [39], Dicontophrya; [40,41] peritrichs. Taxonomy (new family, genus or species), redescription, revision: Apostomatia: [42]; Apostomatida: [43]; Trichodina: [44]; Epistylis and Opercularia: [45]; Spirochona: [46]; Buetschlia and Charonina: [47,48,[49][50][51]31].…”
Section: Introductionmentioning
confidence: 99%